Modeling and simulation of the industrial numerical distance relay aimed at knowledge discovery in resident event reporting - Othman, Mohammad Lutfi; Aris, Ishak; Abdul Wahab, Noor Izzri (Sage Publications, 2014)
In the motivation of tapping the strong potential of computational intelligence in discovering knowledge of protective relay operations using data mining, modeling and simulation of an actual industrial numerical distance relay and its recording facility are a vital requisite. This is justified by the practicality and necessity of divulging the decision algorithm hidden in the recorded relay event report using computational intelligence-based data mining. Thus, this paper studies the detailed modeling and simulation of an industrial AREVA MiCOM P441 distance relay, accommodated together with its own simulated event report recording facility. The idea is to provide the flexibility of allowing the simulated event report to have sufficiently significant depth and breadth for data mining purposes. The modeled relay has operated correctly and discriminatively in deciding circuit breaker pole(s) to be tripped in stipulated assertion times as per the Malaysian licensee’s requirements for various faults and protected zones along a transmission line. It has subsequently been validated successfully by the performance of the real field AREVA MiCOM P441 distance relay belonging to the Malaysian licensee. With the successful modeling and simulation of the AREVA MiCOM P441 distance relay and its recording facility, such subsequent works as data extraction and preparation, computational intelligence-based data mining for relay decision algorithm discovery and finally a relay analysis expert system development can certainly be executed. These subsequent applications are briefly explored as a demonstration of the benefit offered after the successful modeling of the relay.